FISH AND SHELL FISH FAUNA OF THE RETTING AND NONRETT1NG ZONES OF THE KADINAMKULAM KAYAL, KERALA - NANDAN, S. BUOY; AZIS, P.K. ABDUL (Journal of Indian Fisheries Association, 2015)
Retting of coconut husk is one of the major problems of pollution hi the estuaries (kayals)of Kerala. Retting activity has resulted in the mass destruction of the flora and fauna and hasconverted sizeable sections of the kayal into virtual cesspools of foul smelling stagnant waters.Levels of hydrogen sulphide, phosphate and BOD, increased while dissi lived oxygen and fishand shellfish fauna decreased in the ambient waters. In the Kadinamkulam kayal a total of 37species of fishes belonging to 26 families, 5 species of prawn and 2 species each of crabs andmolluscs were recorded from the nonretting zone, whereas only 20 species of fish in deadcondition were collected from the rating zone. Prawns, crabs and molluscs were absent at thevetting zone. IVIajority of the fish fauna in the kayal were marine forms.